PENGEMBANGAN MEDIA POP UP BOOK TEMA 5 PAHLAWANKU PADA MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER KELAS IV SDN 01 GINTUNG - Fitriani, Lutfi; Fajriyah, Khusnul (KALAM CENDEKIA PGSD KEBUMEN, 2018)
Abstract This study aims to determine the success of mining and media feasibility po up book on the model of learning Numbered Head Together. This type of research is research and delevopment (R & D) research. Research and development methods are used to produce specific products and test the validity of a medium. The subjects of this research are 26 students of grade IV of elementary school. The data collected in this study are data of media experts and material experts, and product trial data. The data collection instrument is a questionnaire. The product produced in this research is a pop up media that is designed using corel X.5. Data processing is taken from validation of media expert, material expert, student acceptance questionnaire, and teacher acceptance questionnaire. The result of data analysis on media expert validation is 93% very good, material expert 89% very good, student acceptance questionnaire 88% very good, teacher acceptance questionnaire 96%. It shows the effective pop-up medium used in learning. Based on the results of this development research, the suggestion that researchers can convey is that the pop-up media can be used by the teacher as one of the learning media in the school. Keywords: Pop Up Book, Numbered Head Together Abstrak Penelitian ini bertujuan untuk mengetahui keberhasilan pengambangan dan kelayakan media po up book pada model pembelajaran Numbered Head Together. Jenis penelitian ini adalah penelitian research and delevopment (R&D). Metode penelitian dan pengembangan digunakan untuk menghasilkan produk tertentu dan menguji kevalidan suatu media. Subyek penelitian dalam penelitian ini adalah 26 siswa kelas IV Sekolah Dasar. Data yang dikumpulkan dalam penelitian ini adalah data ahli media dan ahli materi, dan data ujicoba produk. Instrumen pengumpulan data berupa angket. Produk yang dihasilkan dalam penelitian ini adalah media pop up yang di desain menggunakan corel X.5. Pengolahan data diambil dari validasi ahli media, ahli materi, angket keberterimaan siswa, dan angket keberterimaan guru. Hasil analisis data pada validasi ahli media 93% sangat baik, ahli materi 89% sangat baik, angket keberterimaan siswa 88% sangat baik, angket keberterimaan guru 96%. Hal ini menunjukkan media pop up efektif digunakan dalam pembelajaran. Berdasarkan hasil penelitian pengembangan ini, saran yang dapat peneliti sampaikan adalah media pop up dapat digunakan guru sebagai salah satu media pembelajaran di sekolah.Kata kunci: Pop Up Book, Numbered Head Together